2012
DOI: 10.1152/ajprenal.00268.2011
|View full text |Cite
|
Sign up to set email alerts
|

The miR-200 family regulates TGF-β1-induced renal tubular epithelial to mesenchymal transition through Smad pathway by targeting ZEB1 and ZEB2 expression

Abstract: Most chronic kidney injuries inevitably progress to irreversible renal fibrosis. Tubular epithelial-to-mesenchymal transition (EMT) is recognized to play pivotal roles in the process of renal fibrosis. However, a comprehensive understanding of the pathogenesis of renal scar formation and progression remains an urgent task for renal researchers. The endogenously produced microRNAs (miRNAs), proved to play important roles in gene regulation, probably regulate most genes involved in EMT. In this study, we applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
177
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(198 citation statements)
references
References 34 publications
(38 reference statements)
10
177
2
1
Order By: Relevance
“…The relationship between CKD or other pathologically induced kidney diseases and miRNAs, like miR-200a, miR-200b, miR-141, miR-429, miR-205, miR-335, miR-34a and miR-192, has also been studied. [28][29][30][31] These studies have not mentioned miR-494, suggesting that the majority of miR-494 expression appears in the early phase of I/R injury and not in CKD or the other pathologically induced kidney diseases.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between CKD or other pathologically induced kidney diseases and miRNAs, like miR-200a, miR-200b, miR-141, miR-429, miR-205, miR-335, miR-34a and miR-192, has also been studied. [28][29][30][31] These studies have not mentioned miR-494, suggesting that the majority of miR-494 expression appears in the early phase of I/R injury and not in CKD or the other pathologically induced kidney diseases.…”
Section: Discussionmentioning
confidence: 96%
“…It is well documented that ZEB1 is an important transcript factor of EMT by inhibiting an E-box gene, such as E-cadherin. 36 Several previous studies suggest that ectopic expression of miR-200c hinders progression of EMT in TGF-b-treated cells by downregulation of ZEB1 37 and miR-200c induced endothelial cell apoptosis and senescence via ZEB1 inhibition. 38 ZEB1 is induced by TGFb during smooth muscle differentiation, in which it interacts with Smad3 and SRF to transactivate the genes encoding smooth muscle a-actin and smooth muscle myosin heavy chain.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of miRNAs is implicated in EMT modulation [25]. Gregory reported that miRNAs, such as smiR-200 family and miR-205, act as key modulators of EMT and enforcers of the epithelial phenotype targeting ZEB1 and SIP1 [26]. Dong et al demonstrated miR-194 directly targets BMI-1, and reverses EMT phenotype in endometrial cancer cells [27].…”
Section: Discussionmentioning
confidence: 99%